Toward a molecular understanding of adaptive immunity: a chronology – part II - Smith, Kendall A. (Frontiers in Immunology, 2012)
By 1980 it was obvious that to more fully understand adaptive immunity, one needed to somehow reduce the tremendous complexity of antigen recognition by T cell populations. Thus, there were two developments that resulted in a paradigm shift in immunology, one being the generation of monoclonal antibodies, and the other the development of monoclonal functional antigen-specific T cell lines. For the first time, the cellular reagents became available to ask new questions as to how individual cells comprising the complex cell populations recognize and respond to changes in their molecular environments. The first successful generation of monoclonal T cells depended upon the understanding that antigen renders cells responsive to the antigen non-specific T cell growth factor that came to be termed interleukin-2 (IL-2), which could then be used in propagating large numbers of the progeny of single cells, which in turn could then be used for molecular analyses. Monoclonal functional human T cells were used to immunize mice to generate clone-specific (clonotypic) monoclonal antibodies, which then permitted the first biochemical characterizations of the antigen recognition elements of the T cell antigen receptor complex. Moreover, the use of monoclonal cytolytic and helper/inducer human T cell clones essentially proved that the T cell-specific molecules T4 and T8 functioned as accessory molecules in antigen recognition by defining MHC class II or class I restriction respectively. As well, the expression of the T3 molecules, found to be common to all T cells, were shown further to be obligatory for functional antigen-specific T cell signaling. The monoclonal IL-2-dependent T cells were also instrumental in the isolation and purification of the IL-2 molecule to homogeneity, the first interleukin molecule to be identified and characterized. These advances then led to the generation of pure radiolabeled IL-2 molecules that were used to identify the first interleukin cellular re